1990
DOI: 10.1172/jci114768
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-stimulating antibody activity between different immunoglobulin G subclasses.

Abstract: To investigate the distribution of thyroid-stimulating antibody (TSAb) activity between IgG subclasses, sera from 11 patients with Graves disease (including the National Institute of Biological Standards and Control (NIBSC) Research Standard, long acting thyroid stimulator-B) were fractionated by chromatography on affinity columns of monoclonal IgG subclass antibodies or protein A to deplete all but a single subclass. The resulting fractions were 98% or more pure for a single subclass. In all 11 patients, TSAb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
1
4

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(64 citation statements)
references
References 25 publications
4
55
1
4
Order By: Relevance
“…It has been reported that the thyroid-stimulating antibody is IgG 1 [18]. Our previous data that serum IL-10 increases in patients with intractable GD [14] appears to be consistent with this report because IL-10 is also a switching factor for IgG [12,13].…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that the thyroid-stimulating antibody is IgG 1 [18]. Our previous data that serum IL-10 increases in patients with intractable GD [14] appears to be consistent with this report because IL-10 is also a switching factor for IgG [12,13].…”
Section: Discussionsupporting
confidence: 90%
“…These data reinforce the significance of the Th1 immune response in the pathogenesis of Graves' disease that we have previously proposed (3). Although our animal model may not perfectly mimic Graves' disease in humans, data supporting the involvement of the Th1 immune response in Graves' patients, for example, Th1-type TSAb (59), are indeed present. …”
Section: Discussionsupporting
confidence: 82%
“…However, studies on cytokine profiles in thyroid tissues and sera provided controversial data regarding Th1 to Th2 balance [39]. Furthermore, of importance, TSAbs in human sera are of IgG1 subclass (Th1 type in humans) [40].…”
Section: Th1 Versus Th2 Immune Balance In Development Ofmentioning
confidence: 99%